CUTANEOUS LESIONS UNCOVERING SYSTEMIC CRYPTOCOCCOSIS IN AN HIV POSITIVE PATIENT - Pinto-Almeida, Teresa; Rosmaninho, Aristóteles; Amorim, Isabel; Alves, Rosário; Selores, Manuela (Journal of the Portuguese Society of Dermatology and Venereology, 2013)
Cryptococcosis is a systemic infection that affects mainly immunocompromised subjects, occurring in 2-10% of AIDS patients. In this population, the initial phase of respiratory infection is often unrecognized, leading to systemic dissemination and multiorganic involvement. Secondary cutaneous lesions usually occur in the terminal phases of lethally disseminated infections. The authors report the case of a 37-year-old HIV positive man that presented with a 1-week history of cutaneous lesions on the face, trunk and upper limbs, together with fever, cough and severe headache. Laboratory exams and imaging studies allowed the diagnosis of a systemic cryptococcosis with secondary cutaneous involvement and the patient started treatment with systemic amphotericin B and fluconazole, with complete resolution of the clinical picture. This case highlights the fact that cutaneous lesions are often the presenting sign of a systemic cryptococcosis. The unspecific features of these lesions imply a high index of clinical suspicion in order to establish the correct diagnosis and initiate immediate treatment. KEYWORDS – Cryptococcosis; Immunosuppression; HIV.